TREML4 Promotes Inflammatory Programs in Human and Murine Macrophages and Alters Atherosclerosis Lesion Composition in the Apolipoprotein E Deficient Mouse - Gonzalez-Cotto, Marieli; Guo, Liang; Karwan, Megan; Sen, Shurjo K.; Barb, Jennifer; Collado, Carlos J.; Elloumi, Fathi; Palmieri, Erika M.; Boelte, Kimberly; Kolodgie, Frank D.; Finn, Aloke V.; Biesecker, Leslie G.; et al. (Frontiers in Immunology, 2020)
Background: The Triggering Receptor Expressed on Myeloid cells-like 4 (TREML4) is a member of the TREM receptor family, known modulators of inflammatory responses. We have previously found that TREML4 expression positively correlates with human coronary arterial calcification (CAC). However, the role of TREML4 in the pathogenesis of cardiovascular disease remains incompletely defined. Material and Methods: Since macrophages play a key role in inflammation, we investigated if activated macrophages selectively expressed TREML4. Consequently, we performed RNA-seq analysis of human and murine M1-Treml4 expressing macrophages and to further investigate Treml4 contribution to cardiovascular disease, we employed Apolipoprotein E knockout (Apoe-/-) mice. Finally, we performed both transcriptomics and metabolomics analysis of murine oxLDL-loaded macrophages. Results: We found that carriage of either one of the eQTL SNP’s previously associated with increased TREML4 expression conferred higher expression in human inflammatory macrophages (M1) compared to alternatively activated macrophages (M2). Furthermore, we found that TREML4 expression in human M1 affected several inflammatory pathways related to leukocyte activation, apoptosis and extracellular matrix degradation. Similarly, murine M1 expressed substantial levels of Treml4, as did oxLDL treated macrophages. Transcriptome analysis confirmed that murine Treml4 controls the expression of genes related to inflammation and lipid regulation pathways, suggesting an involvement in atherosclerosis. Analysis of Apoe-/-/Treml4-/- mice showed slightly reduced plaque burden and reduced lesion complexity as indicated by decreased stage scores, macrophage content and collagen deposition. Finally, transcriptome analysis of oxLDL-loaded murine macrophages showed that Treml4 represses a specific set of genes related to carbohydrate, ion and amino acid membrane transport. Metabolomic analysis confirmed that Treml4 deficiency may promote a beneficial relationship between iron homeostasis and glucose metabolism. Together, our results suggest that Treml4 plays a role in the development of cardiovascular disease, as indicated by Treml4-dependent dysregulation of macrophage inflammatory pathways, macrophage metabolism and promotion of vulnerability features in advanced lesions.